Quality of multi-row harvesting in sugarcane plantations established from pre-sprouted seedlings and billets - da Silva Gírio, Lucas Augusto [UNESP]; da Silva, Rouverson Pereira [UNESP]; de Menezes, Patricia Candida [UNESP]; Carneiro, Fanciele Morlin [UNESP]; Zerbato, Cristiano [UNESP]; Ormond, Antonio Tassio Santana (My University, 2019)
The mechanical planting and harvesting of sugarcane have experienced great technological transformations in Brazil. A pre-sprouted seedling system launched in 2012 is being used widely throughout the country, and new inter-row spacing configurations have been proposed due to the introduction of new multi-row harvesters. The aim of the present study was to evaluate the quality of the mechanical harvesting of sugarcane as performed by a multi-row harvester in three different planting systems, using statistical process control as a tool. The experiment was performed in an agricultural area located in Guariba, in the state of São Paulo, Brazil. The quality of harvesting performed by a multi-row harvester was evaluated in three different planting systems: PSS1, pre-sprouted seedlings with row spacing of 1.25 m; PSS2, pre-sprouted seedlings spaced 1.50 m; and BIL, billets with spaced 1.50 m. The planting material (billet or seedling) and spacing between rows affected the harvesting process. PSS1 presented the lowest process variability for all the evaluated quality indicators except for the damage index. The harvesting process was stable for the cutting height, damage index and soil penetration resistance. BIL presented the highest process variability, and its harvesting process was only stable for the loss index and soil penetration resistance.
Keywords: Damage index; Saccharum spp.; Spacing; Statistical process control